Assessing the Use of Iron Oxide and Silica in Industrial Wastewater Treatment - Fahad Agaba (Uganda Christian University, 2025)
Lake Victoria, the world’s largest tropical freshwater lake, supports critical ecological, economic and social functions across East Africa. However, increasing industrial pollution, particularly in Walukuba Masese (Jinja district), poses a serious threat. The uncontrolled discharge of untreated effluent especially from the sunbelt textile industry has led to elevated phosphorous levels, causing eutrophication, harmful algal blooms and aquatic degradation. This study investigates the use of iron oxide and silica, as a sustainable method for phosphorous removal from industrial waste water. Laboratory experiments assessed adsorption efficiency based on parameters such as contact time, adsorbent dosage, Ph, and initial phosphorous concentration. The adsorption mechanism relies on Fe-O-P bond formation, where phosphates ions interact with hydroxyl groups on iron oxide surfaces. Silica enhances this process by increasing surface area structural stability. Finding reveals that the iron oxide and silica combination offers a cost effective and environmentally sustainable alternative to conventional treatment methods. Significant reductions in phosphorous levels were observed, demonstrating the potential of this system to meet regulatory standards and protect Lake Victoria’s aquatic ecosystem. This research highlights the importance of adopting innovative, efficient wastewater treatment technologies for long term water resource sustainability.
Undergraduate